Discussion on the Inconsistency of Central Bank Independence Measures - Aleksandra Maslowska (Aboa Centre for Economics (ACE), 2007)
In recent years, a number of countries have modified their monetary institutions, focusing, in many cases, on increasing of the independence of national central banks. This attracted attention of academics and policymakers, who have shown continuing interest in various monetary institutions with respect to the formulation of monetary policy. This paper analyzes some of them. Especially, it reviews and criticizes generally accepted indices of central bank independence. The analysis names several imprecisions among measures that cover the subjectivity, criteria and weighting problem. It brings the conclusion that neither of measures, whether it is the widely accepted Cukierman index (1992) or work based on Grilli, Masciandaro and Tabellini (1991), are not free of criticism. Additional problem appears when countries with different levels of development are concerned. Here, the Borda Count method is used among ten transition economies to determine the country with the most independent central bank, based on four different measures. With the wide criticism of indices, this work questions the robustness and representation of empirical studies and their results.
Keywords: E50; 330; institution; central bank independence